Assessment of Performance Based on Malcolm Baldrige Criteria For Performance Excellent In The In-Patient Unit at Islamic Hospital Mabarrot Gresik - Setya Haksama; Muhammad Farid Dimjati Lusno; Diansanto Prayoga; Muhammad Azhary, RN; Shyamkumar Sriram; Arga Setyo Adji; Abdillah Maulana Satrioaji; Abdullah Al Mamun; Syahprevi Rayyan Zeinsar (YCAB Publisher, 2026)
Background: Hospital service performance plays a crucial role in healthcare competition, as it directly influences patient satisfaction, operational efficiency, and the reputation of the institution. In a competitive healthcare environment, hospitals are continuously striving to improve their service quality and operational outcomes. Performance assessment is essential to assess the effectiveness of hospital management and identify areas for improvement. Objective: Hospital service performance is a critical factor in market competition. Strong performance reflects the hospital's success, making performance assessment essential for continuous improvement Methods: This observational and analytical study uses a cross-sectional approach. The MBCfPE criteria were used as the performance assessment variable. Data were collected from 34 respondents out of 120 employees at the hospital. Results: The performance scores based on the MBCfPE criteria showed that the organizational profile scored 88.97, which is not included in the overall MBCfPE calculation. The leadership criteria scored 62.50, indicating a need for improvement. On the other hand, several criteria scored excellently, including strategic planning (93.86), customer focus (95.37), assessment, analysis, and knowledge management (90.28), human resources focus (97.97), operational activities focus (99.99), and results (97.65). The overall performance score for Islamic Hospital Mabarrot Gresik was 637.56, which falls within the range of 576–675 on the MBCfPE scale, placing it in the Industry Leader category. Despite the good score, the findings indicate that leadership and strategic planning require attention for further improvement to achieve a higher level of organizational performance. Conclusion: The performance of Islamic Hospital Mabarrot Gresik is at an average level, with leadership and strategic planning requiring significant improvement. To enhance organizational performance, focused efforts should be directed towards these criteria, ensuring a thorough and effective implementation of the MBCfPE criteria. Keywords: Hospital performance; Malcolm Baldrige; MBCfPE; organizational performance; healthcare quality